Factors Affecting Evaporation from a Subarctic Tundra, Churchill, Manitoba - Dobson, Monika M. (1980)
Evaporation was calculated for a subarctic beach ridge, near Churchill, Manitoba, using the energy balance approach. Energy balance calculations for the measurement season revealed an average Bowen ratio, β, of 0.68, with a value of 1.00 representing α' (the evaporability parameter). Fifty-seven percent of the net radiation was utilized by the evaporative heat flux over this tundra surface. Regressions were used to determine the most likely combination of environmental variables responsible for the behaviour of evaporation. Surface soil moisture remained relatively constant throughout the summer measurement period and soil temperatures appeared to be unrelated to evaporation. Air temperature proved to be insignificant to the evaporation flux, and net radiation alone could only account for 54% of the variability. The combination of the net radiation and the wet and dry bulb temperature depression at 1 m accounted for 88% of the variability of the evaoorative heat flux. The mean α' for a site is assumed to be controlled by the surface type in simplified variations of the combination model. The conclusion has been drawn from this study that the variability of α' can be accounted for by variable atmospheric humidities as well as net radiation. The importance of this atmospheric control on the rate of evaporation is emphasized. Thesis Master of Science (MSc)